Transforming Surgical Practices with Computer Vision: Recent Developments and Clinical Applications - Cunha Reis, Tiago (Gazeta Médica, 2024)
Computer vision has emerged as a transformative technology with the potential to significantly enhance surgical practices' safety, efficiency, precision, and training. By leveraging advanced algorithms and artificial intelligence, computer vision applications offer real-time analysis of visual data during surgical procedures, enabling automated decision support, performance assessment, and intraoperative guidance. This article delves into the recent developments in computer vision technology within the realm of surgery, particularly focusing on its application in minimally invasive procedures. It also discusses the current state of computer vision in surgery while exploring its practical applications. The article highlights the challenges that must be overcome for widespread clinical adoption, emphasizing the crucial role of collective efforts in addressing these obstacles. With a balanced focus on both the technical advancements and the practical implications, this manuscript provides a comprehensive overview of the role of computer vision in modern surgery.